Can Serum Lactate Dehydrogenase Levels be used as a Diagnostic Tool for Hemolytic Hyperbilirubinemia in Neonates? - Muhammad Tauseef Rauf, Bushra Fatima, Mazhar Qadir Khan, Ayesha Khanum, Nisar Ahmad, Khawaja Ahmad Irfan Waheed, (Pakistan Journal of Medical & Health Sciences, 2023)
Background & Objective: Neonatal jaundice is common reason for admission in neonatal units requiring further evaluation to prevent adverse neurodevelopmental outcome. Lactate dehydrogenase levels are high in hemolysis. This study was aimed to explore the diagnostic properties of Lactate Dehydrogenase (LDH)in hemolytic causes of neonatal hyperbilirubinemia. Methods: In this observational cross sectional study, prospective data was collected at Neonatology department of The Children’s Hospital and University of Child Health, Lahore fromFebruary 2020 to March 2022. A total of 364 neonates with the diagnosis of indirect hyperbilirubinemia were enrolled through convenient sampling method after excluding the comorbidities and sick neonates.The neonates were categorized into hemolytic and non-hemolytic group and lactate dehydrogenase levels were compared in both the group. Data was analyzed using SPSS version 24 Results: Out of 364 babies, 123 (33.79%) were diagnosed as having hemolytic jaundice while 241 (66.21%) fell in non-hemolytic group. Out of 123 newborns in hemolytic jaundice group, LDH levels of 101 (82.1%) newborns were raised while only 124 (51.5%) newborns in non-hemolytic group (241) had raised LDH (p-value <0.001). Sensitivity and Specificity of LDH levels as marker of hemolysis was 82.11% and 48.55% and positive predictive value and negative predictive value were 44.89% and 84.17% respectively. The practical implication that there are insufficient test s in common clinical usage that cal reliability make the the diagnosis of hemolysis Conclusion: LDH is an effective diagnostic tool for the diagnosis of hemolytic hyperbilirubinemia in neonates with a higher sensitivity and negative predictive value. Keywords: neonatal hyperbilirubinemia, hemolytic jaundice,lactate dehydrogenase